2015
DOI: 10.1080/19443994.2014.890132
|View full text |Cite
|
Sign up to set email alerts
|

Removal of textile-based dyes by nanofiltration: study of physicochemical parameters’ effect on the retention by experimental designs methodology

Abstract: A B S T R A C TThis paper focuses on nanofiltration (NF) process mainly in the retention of colored effluents chemicals and dyes as they are rejected from textile plants. The purpose of this work is to study the effect of initial dye concentration, pH, salt presence, conversion rate, and transmembrane pressure (PTM) on Basic Green 4 and Basic Yellow 2 retention by NF. Tangential filtration mode through a composite membrane NF270 type Dow FILMTEC was used in the experiments. Experimental designs such as full fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Various techniques have been applied for the removal of azo-dyes from aqueous solutions, including extraction [9], coagulation and flocculation [10], adsorption [11,12], biosorption [12], coprecipitation [13], sonochemical [14] and electrochemical [15] degradations, membrane processes (micellar enhanced ultrafiltration [16], nanofiltration [17], and ion exchange [18]), advanced oxidation processes (Fenton [19] and UV/H 2 O 2 photodegradation [20]), and integrated treatments [21].…”
Section: Desalination and Water Treatmentmentioning
confidence: 99%
“…Various techniques have been applied for the removal of azo-dyes from aqueous solutions, including extraction [9], coagulation and flocculation [10], adsorption [11,12], biosorption [12], coprecipitation [13], sonochemical [14] and electrochemical [15] degradations, membrane processes (micellar enhanced ultrafiltration [16], nanofiltration [17], and ion exchange [18]), advanced oxidation processes (Fenton [19] and UV/H 2 O 2 photodegradation [20]), and integrated treatments [21].…”
Section: Desalination and Water Treatmentmentioning
confidence: 99%
“…At high pH (> 10), they bond with hydroxyl and carboxyl groups in the membrane. Hence, there is a decrease in charge density on the membrane surface, which leads to lesser repulsion of the dye molecules and subsequently lesser rejection with increasing pH . Some researchers have come up with the theory that reactive dyes hydrolyze at high pH conditions, where these hydrolyzed dyes are better able to permeate through the membranes .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the dye permeance of our membrane is higher than most of the other membranes listed in Table 4, which indicates that the retention of Congo red is achieved with a lower energy consumption. The effect of transmembrane pressure on the rejection of various dyes by NF membranes has been investigated by different groups [32][33][34][35]. In all these studies, an increase in dye rejection was observed with increased pressure.…”
Section: Dye Removal Performance Of Nf Membranementioning
confidence: 99%